The interference of a rearward facing jet on the flow over three representative afterbody shapes in a uniform subsonic flow - Craven, A. H. (College of Aeronautics, 1957)
This report contains the results of an experimental investigation into the interference of a ,rearward facing undeflected jet on the flow over three afterbody shapes at subsonic speeds. The tests were performed at a Reynolds number of 0.3 x 10(6) based on body diameter. It was found that the form (or pressure) drag coefficient of the bluff afterbody of a right cylinder increased appreciably with increase in jet thrust coefficient. A similar but much smaller increase in form drag was found on an ellipsoidal afterbody and a 'boat-tail'. The effect of the jet was found to extend to approximately three body diameters upstream of the jet exit but that beyond one body diameter the effect was very small.